THE INFLUENCE OF EMPLOYEE ENGAGEMENT ON INNOVATIVE WORK BEHAVIOR IN EMPLOYEES GEN Z SPECIAL REGION OF YOGYAKARTA WITH WORK LIFE BALANCE AS AN INTERVENING VARIABLE - Cintana Puti Divani; Nur Wening (International Journal of Business, Law and Political Science, 2024)
The study aims to analyze the effect of employee engagement on innovative work behaviour with work life balance as an intervening variable. This research uses Incidental sampling technique with total of 65 respondents with the criteria of Gen Z employees aged 18-26 years who live and work in the Daerah Istimewa Yogyakarta. The test used in this study are descriptive analysis, instrument test (validity test and reliability test), classical assumption test, coefficient of determination, hypothesis test (t test), and path analysis using the sobel test. The independent variable in this study is employee engagement. The intervening variable in this study is work life balance. The dependent variable in this study is innovative work behavior. The results of this study indicate that, employee engagement has positive and significant effect on work life balance, work life balance has positive and significant effect on innovative work behavior, employee engagement has positive and significant effect on innovative work behavior, and work life balance partially mediates the relationship between employee engagement and innovative work behavior.